Correction: Management of chronic Hepatitis C at a primary health clinic in the high-burden context of Karachi, Pakistan. - Yuely A Capileno; Rafael Van den Bergh; Dmytro Donchuk; Sven Gudmund Hinderaker; Saeed Hamid; Rosa Auat; Gul Ghuttai Khalid; Razia Fatima; Aashifa Yaqoob; Catherine Van Overloop (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0175562.].